2015
DOI: 10.1155/2015/727291
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Nuclear Power Plants for Liquefaction Consequences

Abstract: In case of some nuclear power plants constructed at the soft soil sites, liquefaction should be analysed as beyond design basis hazard. The aim of the analysis is to define the postevent condition of the plant, definition of plant vulnerabilities, and identification of the necessary measures for accident management. In the paper, the methodology of the analysis of liquefaction effects for nuclear power plants is outlined. The procedure includes identification of the scope of the safety analysis and the accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…If the hazard could not be neglected, the consequences of liquefaction should be thoroughly analysed, and the plant safety should be justified. Paks NPP in Hungary is an example of this case; see Katona et al [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…If the hazard could not be neglected, the consequences of liquefaction should be thoroughly analysed, and the plant safety should be justified. Paks NPP in Hungary is an example of this case; see Katona et al [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Among the commonly used cyclic stress-based methods, the CPT-based method of Boulanger and Idriss is deemed to be the most accurate and most realistic. On one hand, SPT testing has no tradition in Hungary and contractors has no practice in performing them, hence the results often turned out to be erroneous as it was also pointed out by Katona et al [9]. On the other hand, independent comparison of CPT-based methods by Green et al [10] showed that the procedure proposed by Idriss and Boulanger [11] -which was updated in 2014results in the lowest error index for the case histories that were analyzed from the Canterbury Earthquake Sequence, New Zealand.…”
Section: Back-analysis Of Dunaharaszti Earthquake Peak Ground Accelerationmentioning
confidence: 99%
“…For the evaluation of the consequences of differential settlement, useful experiences have been gained from the linear and non-linear analysis performed for the case of liquefaction for Nuclear Power Plant Paks, Hungary [29]. Although the physical phenomena of liquefaction and PGD is differing, the differential settlement in both cases cause similar static demand on the structure.…”
Section: Studies Contributing To Understanding the Case Of Plant Resp...mentioning
confidence: 99%